Tree component structure and dispersion strategies in a subtropical forest along a topographic sequence in Alto- Uruguai Estrutura e estratégias de dispersão do componente arbóreo de uma floresta subtropical ao longo de uma topossequência no Alto-Uruguai - Souza K.* (2015)
This study aimed to analyze the floristic-structural composition and dispersion strategies of the arboreal component along a topographic sequence in a subtropical forest in Alto-Uruguay region. For this, a total of 50 200 m' plots were allocated into three sectors within a forest fragment, defined according to the distance from a dam reservoir and slope: lower sector, next to the reservoir and average slope of 14.38° ('2.64), intermediate sector, with an average slope of 19.74° ('1.98), and upper sector, near to the ridge, with average slope of 20.66° ('1.24). All sampled tree species individuals with circumference at breast height (CAP) ≥ 15.7 cm were measured (CAP) and identified. All species were classified according to their dispersion syndrome. The data were analyzed through the Shannon (H') and Pielou indexes, NMDS (Nonmetric Multidimensional Scaling), PERMANOVA (Permutational multivariate ANOVA), Indicator Species Analysis and contingency table. A total of 1,562 individuals, belonging to 69 species were sampled, with lower sector presenting the lowest diversity and the highest dominance The ordination of data showed floristic-structural differences among sectors, confirmed by PERMANOVA test (p < 0.001). Four species were indicative of the lower sector, one of the intermediate and five of the upper sector. Despite zoochory prevailing among sectors, the individuals of species with different dispersal syndromes were not evenly distributed across sectors. We conclude that the topography represented an important source of tree component variation, influencing species distribution, and diversity pattern and dispersal syndrome representativeness.